Improved Ophthalmic Outcomes Following Venous Sinus Stenting in Idiopathic Intracranial Hypertension - Oyemade, Kafayat A.; Xu, Timothy T.; Brinjikji, Waleed; Cutsforth-Gregory, Jeremy K.; Lanzino, Giuseppe; Kallmes, David F.; Moss, Heather E.; Dodd, Robert; Bhatti, M. Tariq; Chen, John J. (Frontiers in Ophthalmology, 2022)
Background Ophthalmic outcomes following venous sinus stenting (VSS) in patients with idiopathic intracranial hypertension (IIH) are not well characterized. Materials and Methods A retrospective chart review was conducted on 86 consecutive patients with IIH who underwent venous sinus stenting at Mayo Clinic, Rochester, Minnesota and Stanford Medical Center, Palo Alto, California between May 2015 and October 2021. Patients with raised intracranial pressure from a non-IIH etiology were excluded. Clinical symptoms and neuro-ophthalmological data, including best corrected visual acuity (BCVA), visual field mean deviation, papilledema, and optical coherence tomography (OCT) peripapillary retinal nerve fiber layer (pRNFL) and ganglion cell inner plexiform layer (GC-IPL), were analyzed. Baseline measurements before VSS and 3 months or more postoperatively were compared. Results Eighty-six subjects (82 female) were included in this study, with a median age of 33 (16–68) years and a median body mass index of 36.69 (22.30–62.00) kg/m2. 85/86 (98.8%) had attempted prior management with medication, and 12/86 (14%) had prior surgical management with optic nerve sheath fenestration, ventriculoperitoneal shunt, or bariatric surgery. Prior to VSS, 67/86 (77.9%) had papilledema, 85/86 (98.8%) had headaches, and 68/86 (79.1%) had pulsatile tinnitus. For patients with both pre- and post-VSS data available, the average papilledema grade was 1.76 (0–5) (n = 74) and the average OCT pRNFL was 186.34 (52.00–588.00) µm (n = 70), prior to VSS. A median of 4.0 (interquartile range 3.3–5.4) months after VSS, the average papilledema grade improved to 0.39 (0–2), p <0.001, and OCT pRNFL improved to 96.86 (47.00–168.00) µm, p <0.001. 28/86 (32.6%) patients no longer required medication for high intracranial pressure. 14/85 (16.5%) patients reported complete resolution of their headache and 55/71 (77.5%) reported improvement in headache quality. 40/68 (66.7%) reported complete resolution of pulsatile tinnitus. OCT GC-IPL, BCVA, and visual field mean deviation did not significantly change pre- vs post-VSS. Conclusions Our large consecutive case series corroborates smaller prior studies in demonstrating the overall efficacy of VSS for patients with IIH. We found both ophthalmic improvements, as demonstrated by the significantly reduced papilledema and pRNFL, and overall clinical symptom improvement.